2017
DOI: 10.31142/ijtsrd7012
|View full text |Cite
|
Sign up to set email alerts
|

WASH Water, Sanitation and Hygiene : A Review

Abstract: WASH is related to any country's concern in relation to the health of their people. It becomes the right of the citizen to acquire safe water, sanitation and hygiene measures. WASH are among the most crucial for human to create healthy life. WASH interventions aim to prevent and control transmission of bacteria, viruses and parasites. The poor and unsafe access to WASH plays a key role in transmission of various diseases. Since independence India is struggling to prevent OFD, and provide good sanitation. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As bacteria are unable to take up tetrahydrofolic acid from their surroundings, inhibition of dihydrofolic acid synthetase will starve the bacteria of thymidine and uridine. These two nucleosides are required for DNA replication and transcription, therefore cell growth and division is disrupted, and thus provides enough time for the body's own immune system to eliminate the bacterial threat [26] The nature of bonding and structure of azomethine organic compounds were elucidated by the elemental analysis, UV-Vis, FTIR, Melting Point, NMR, Chromatography and Molar ratio methods Gomathi et.al were prepared 4-(3-ethoxy-2-hydroxy benxzelideneaminno-N-(thiazole-2-yl-) benzene sulfonamide [24] , Mohamed et.al and were prepared 4-(-phenyl-propylideneamino)-benzenesulfonamide [25] . In accordance with the data obtained from antibacterial activities (1-carboxy-2-(4-hydroxyphenyl)ethyl) imino) methyl) -2-hydroxy benzoic acid were highly inhibited the growth of tested fungi.…”
Section: Antifungal Bioassaymentioning
confidence: 99%
“…As bacteria are unable to take up tetrahydrofolic acid from their surroundings, inhibition of dihydrofolic acid synthetase will starve the bacteria of thymidine and uridine. These two nucleosides are required for DNA replication and transcription, therefore cell growth and division is disrupted, and thus provides enough time for the body's own immune system to eliminate the bacterial threat [26] The nature of bonding and structure of azomethine organic compounds were elucidated by the elemental analysis, UV-Vis, FTIR, Melting Point, NMR, Chromatography and Molar ratio methods Gomathi et.al were prepared 4-(3-ethoxy-2-hydroxy benxzelideneaminno-N-(thiazole-2-yl-) benzene sulfonamide [24] , Mohamed et.al and were prepared 4-(-phenyl-propylideneamino)-benzenesulfonamide [25] . In accordance with the data obtained from antibacterial activities (1-carboxy-2-(4-hydroxyphenyl)ethyl) imino) methyl) -2-hydroxy benzoic acid were highly inhibited the growth of tested fungi.…”
Section: Antifungal Bioassaymentioning
confidence: 99%
“…1 Annual net cost of diarrhea and acute respiratory infections (ARI) is $23 billion per year, while estimated cost of a national hand-washing program is $62 million which would bring a huge saving. 2 Children are vulnerable to soil-transmitted helminth (STH) infections which are recognized as one of the most important causes of stunting in children. Hand washing can reduce the risk of STH as well as ARI.…”
Section: Introductionmentioning
confidence: 99%
“…3 Various studies in lower and middle socioeconomic countries have demonstrated variable results regarding hand washing space, soap for handwashing and knowledge regarding hand washing practice. [2][3][4] Government of India launched Swachh Bharat Swachh Vidyalaya program, which also provided guidelines for hand washing i.e., availability of soap at hand washing station, hand washing to be done before mid-day meal and also after use of toilet or urinal. All children including those facing disability must be able to access and use the facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Water is not only an important factor of public health, but also of general livelihoods and development: crop production, livestock production, industry, commerce and daily life depend on access to water. Water-supply and sanitation conditions therefore directly affect health and food security and are key components in the fight against Hunger and Malnutrition (as cited in [3]). Having access to clean water is often neglected and not understood completely.…”
Section: Introductionmentioning
confidence: 99%